Mothers, Stepmoms and the Brave, New Family. Intercultural Remake and Melodrama: an Analysis of American Stepmom and its Bollywood Remake - Fábics, Natália (Acta Universitatis Sapientiae, Film and Media Studies, 2013)
The Bollywood remake of the American weepie Stepmom (Chris Columbus, 1998) is a fine and rather recent example of the intercultural remake phenomenon, a study topic that is gaining more and more attention. With the aim of suggesting conclusions generally applicable to intercultural remakes, starting from the genre, through characterization, film style and narrative, the present paper examines the remake process in the case of We Are Family (Siddharth Malhotra, 2010) and Stepmom.
https://katalog.adlr.link/Record/ai-53-126495